Nanosurface‐Reconstructed Fuel Electrode by Selective Etching for Highly Efficient and Stable Solid Oxide Cells - Yueyue Sun; Jun Zhou; Jiaming Yang; Dragos Neagu; Zhengrong Liu; Chaofan Yin; Zixuan Xue; Zilin Zhou; Jiajia Cui; Kai Wu (Advanced Science)
Abstract Solid oxide cells (SOCs) are promising energy‐conversion devices due to their high efficiency under flexible operational modes. Yet, the sluggish kinetics of fuel electrodes remain a major obstacle to their practical applications. Since the electrochemically active region only extends a few micrometers, manipulating surface architecture is vital to endow highly efficient and stable fuel electrodes for SOCs. Herein, a simple selective etching method of nanosurface reconstruction is reported to achieve catalytically optimized hierarchical morphology for boosting the SOCs under different operational modes simultaneously. The selective etching can create many corrosion pits and exposure of more B‐site active atoms in Sr2Co0.4Fe1.2Mo0.4O6‐δ fuel electrode, as well as promote the exsolution of CoFe alloy nanoparticles. An outstanding electrochemical performance of the fabricated cell with the power density increased by 1.47 times to 1.31 W cm−2 at fuel cell mode is demonstrated, while the current density reaches 1.85 A cm−2 under 1.6 V at CO2 electrolysis mode (800 °C). This novel selective etching method in perovskite oxides provides an appealing strategy to fabricate hierarchical electrocatalysts for highly efficient and stable SOCs with broad implications for clean energy systems and CO2 utilization.